POLITICAL COMMUNICATION AND GENDER REPRESENTATION FROM A LOCAL CULTURAL PERSPECTIVE - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze how local culture shapes patterns of gender representation in the political communication of political actors in Indonesia.narrative reviewThis study synthesizes various literatures from the perspectives of political communication, cultural studies, and gender studies to understand the relationship between local cultural values ​​and the construction of gender representation. The review shows that local culture plays a central role in determining how gender identities are constructed, negotiated, and displayed in political practice. In the Javanese cultural context, gender representation is often tied to patriarchal structures and refined norms, while Minangkabau culture emphasizes the legitimacy of female leadership through matrilineal traditions. In Bugis, the concept of bissu demonstrates a more inclusive diversity of gender expressions, while Balinese culture displays a balance of purusha pradhana values ​​that still contain gender hierarchies. This study also finds that culturally based political communication strategies through traditional symbols, local rhetoric, and gender imagery are used by political actors to build legitimacy. Furthermore, local and national media play a significant role in framing gender representation according to the cultural context of each region. Overall, this study confirms that gender representation in Indonesian politics is contextual and cannot be separated from the local cultural constructions that exist within society.